Numerical and experimental study of the behavior of a polyamide during the ECAE process using a 105° die (Fracture and Structural Integrity, 2026)
Among the various severe plastic deformation techniques, Equal Channel Angular Extrusion (ECAE) is a widely used method that introduces significant plastic deformation into a sample by forcing it through two intersecting channels, without substantially altering its overall dimensions. In this work, the behavior of polyamide (PA 6.6) under single-turn and double-turn ECAE (1-ECAE and 2-ECAE) was investigated using finite element analysis with a 105° die. Experimental results on PA 6.6 are also presented. The analysis focused on the influence of the channel angle, the intermediate channel length, and friction on equivalent plastic strain distribution and pressing force. The results indicate that using adequate intermediate channel length enhances strain homogeneity, while friction exerts a moderate effect but can lead to localized strain concentration near the die walls. Therefore, proper lubrication is recommended to stabilize material flow, reduce tool wear, and improve process reliability. These findings provide optimized processing parameters for PA 6.6 extrusion and open up new perspectives for enhancing its mechanical performance and expanding its industrial applications.
Keywords: ECAE; Polyamide; Finite element analysis; Equivalent Plastic Strain; Friction